Kegiatan Kampus Mengajar Dalam Memanfaatkan Sampah Salah Satunya Membuat Eco Enzim Dengan Cara Dengan Mendaur Ulang Sampah Organik - Dea Restu Pramudita; Astri Widyaruli Anggraeni (Jurnal Kemitraan Masyarakat, 2024)
Garbage is a dangerous object that can also kill people. Currently, news is circulating on television that the amount of inorganic waste and organic waste is increasing. Therefore, humans need good and correct waste processing so that this does not result in damage to the environment and ecosystem around us. If we reduce waste by recycling inorganic waste and inorganic waste then natural damage or other disasters will not occur. Therefore, recycling waste is very important for humans.